The Challenger disaster : tragedy in the skies - Naujokaitis, Pranas T. (History comics (First Second (Firm)), 2020)
Far in the future on Challenger Day, the day to honor the crew of the Space Shuttle "Challenger," a group of kids aboard the Space Station Sagan present a class presentation about the Challenger disaster. They share information about the history of the Space Shuttle Program, the design of the space shuttle, the "Challenger" crew and their training, the launch, the investigation into the explosion, and the lasting impact of the accident on humanity.